THE ROLE OF PPAT IN TAX OBLIGATIONS FOR THE PARTIES IN THE SELLING OF LAND RIGHTS - I Putu Gede Andhyaksa; I Gusti Agung Ramadana (Warmadewa Press, 2023)
This study discusses the role of Land Deed Making Officials (PPAT) related to tax obligations for parties in the sale and purchase of land rights in Denpasar City and the application of the authority of the Denpasar City Regional Revenue Agency (Bapenda) in determining tax obligations on the Value of Land Rights Acquisition Fees and Buildings (BPHTB) for buyers. This study is empirical legal research with a sociological approach and a conceptual approach. The data sources consisted of: primary, and secondary. The data analysis used in this study is descriptive qualitative. The results show that the Land Deed Official can only sign the Deed of Transfer of Rights to Land and/or Buildings after the Taxpayer submits proof of tax payment and assists the parties to fulfill their tax obligations from the transaction of transfer of rights to land and/or buildings and acts as supervision, controlling, reporting, and facilitating the BPHTB payment process. Another role is that PPAT can help submit requests for information on land market prices based on the will and power of the parties. The application of the authority of the Denpasar City Regional Revenue Agency (Bapenda) in determining tax obligations on the Value of Customs on Acquisition of Rights on Land and Buildings (BPHTB) for buyers who are not listed in the legislation is the use of the indicated price of Land Value (market price) as the basis for calculating BPHTB if the value of the agreement or the price of the sale and purchase transaction of the parties is lower than the price indicated by the value of the land issued by the Denpasar City Bapenda.